2005
DOI: 10.1128/jb.187.15.5419-5426.2005
|View full text |Cite
|
Sign up to set email alerts
|

YycH Regulates the Activity of the Essential YycFG Two-Component System in Bacillus subtilis

Abstract: Of the numerous two-component signal transduction systems found in bacteria, only a very few have proven to be essential for cell viability. Among these is the YycF (response regulator)-YycG (histidine kinase) system, which is highly conserved in and specific to the low-G؉C content gram-positive bacteria. Given the pathogenic nature of several members of this class of bacteria, the YycF-YycG system has been suggested as a prime antimicrobial target. In an attempt to identify genes involved in regulation of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
95
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(103 citation statements)
references
References 28 publications
(30 reference statements)
6
95
0
1
Order By: Relevance
“…An example of such a system might be YycHGF of B. subtilis. YycH, which is located external to the cell membrane, has been proposed to function as an extracellular sensor that confers its activity to the HK YycG (Szurmant et al, 2005). Another possibility is that the truncated HKs are relieved from sensory constraints and are therefore more active than their non-truncated orthologues.…”
Section: Differences In Tcss Within the B Cereus Groupmentioning
confidence: 99%
“…An example of such a system might be YycHGF of B. subtilis. YycH, which is located external to the cell membrane, has been proposed to function as an extracellular sensor that confers its activity to the HK YycG (Szurmant et al, 2005). Another possibility is that the truncated HKs are relieved from sensory constraints and are therefore more active than their non-truncated orthologues.…”
Section: Differences In Tcss Within the B Cereus Groupmentioning
confidence: 99%
“…The best-studied example of cross talk in this system is between YycFG and the PhoPR phosphate limitation TCS in Bacillus subtilis (21,22). In addition, the YycFG TCS includes several auxiliary proteins in its complex regulatory circuits, making it in fact at least a four-component regulatory system in some bacterial species (34,45,46). However, recent studies have shown that there are instances where the YycFG TCS appears not to be essential in some bacterial systems (see below) (11,26,32).…”
mentioning
confidence: 99%
“…1). The different names for the YycG and VicK histidine kinases coincide with different structural features (34,45,46,48) (Fig. 1).…”
mentioning
confidence: 99%
“…Celine Fabret found a single system essential for growth whose transcription was repressed upon the initiation of sporulation (11). The genes for the kinase, YycG, and the response regulator, YycF, were in an operon with proteins of unknown function, YycI and YycH, later revealed to be activity regulators of YycG kinase, not transcription regulators (83). A temperature-sensitive YycF mutant stopped growth within 30 min, and microscopy revealed that cells were devoid of internal contents, suggesting leakage through the cell wall and membrane barriers.…”
Section: An Essential Two-component System Connecting Cell Wall Growtmentioning
confidence: 99%